2020
DOI: 10.1186/s12912-020-00464-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of two nurse-based screening tools for delirium in elderly patients in general medical wards

Abstract: Background: Delirium is an acute disturbance characterized by fluctuating symptoms related to attention, awareness and recognition. Especially for elderly patients, delirium is frequently associated with high hospital costs and resource consumption, worse functional deterioration and increased mortality rates. Early recognition of risk factors and delirium symptoms enables medical staff to prevent or treat negative effects. Most studies examining screening instruments for delirium were conducted in intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
10
0
2
Order By: Relevance
“…Other relevant characteristics such as age and SAPS2 were also similar to those in the referred study, showing the representativity of our results. The Nudesc score, used to diagnose delirium in our study, is a validated tool with high specificity for delirium [ 14 , 15 , 16 ]. Known predictors of delirium (age, dementia, alcohol abuse) correlated nicely with delirium detected in this registry and patients with delirium had longer ICU stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other relevant characteristics such as age and SAPS2 were also similar to those in the referred study, showing the representativity of our results. The Nudesc score, used to diagnose delirium in our study, is a validated tool with high specificity for delirium [ 14 , 15 , 16 ]. Known predictors of delirium (age, dementia, alcohol abuse) correlated nicely with delirium detected in this registry and patients with delirium had longer ICU stays.…”
Section: Discussionmentioning
confidence: 99%
“…The Nudesc is routinely assessed by specially trained nurses for all patients on our ICU at least three times a day. The NuDesc is approved, easy to use and has a reported sensitivity (93–98%) and specificity (81–87%) for diagnosis [ 14 , 15 , 16 ]. Delirium positive days were defined as the ratio of days with a positive delirium assessment to all days on which an assessment was possible.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, Bergjan et al showed a high sensitivity (98%) and specificity (87%) in elderly patients in general medical wards. 36 Although data exists showing good performance of the NuDesc when compared to other screening scores, we cannot exclude that findings might have been different when using another score for screening. 19,37 Likewise, there have been studies suggesting that the modified RASS as suggested by the Veteran's Affairs Delirium Working Group might have been even more suited than the RASS for sub classification of delirium although RASS itself is highly associated with delirium.…”
Section: Limitationsmentioning
confidence: 91%
“…O estudo observacional prospectivo, realizado em 2020, com 745 pacientes, com 65 anos ou mais, demostrou que os pacientes que desenvolveram delirium era mais velhos e permaneciam por mais tempo nas unidades médicas quando comparado ao grupo de pacientes não delirantes. As principais causas de admissão hospitalar desses pacientes foram as doenças do sistema circulatório, 73%, e do sistema nervoso, cerca de 16%, seguidas de doenças do sistema respiratório e doenças infecciosas e parasitárias, ambas com a média de 3% das admissões (Bergjan et al, 2020).…”
Section: Discussionunclassified